Peranan Teknologi Informasi dan Komunikasi (TIK) dalam Pertumbuhan Ekonomi di Provinsi DKI Jakarta - Gemawaty, Cut Asiana (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Economic growth in DKI Jakarta Province is increasingly influenced by the development of Information and Communication Technology (ICT). The use of ICT has opened up new opportunities and provided positive impacts in various aspects. Innovation in business, development of a start-up ecosystem, expansion of e-commerce, increased access to education, efficiency of public services, adequate connectivity, and increased mobility are some of the results of ICT integration. However, challenges such as cyber security, access gaps, and the role of government that needs to continue to be strengthened also need to be considered. Therefore, suggestions are directed at improving ICT infrastructure, providing support to start-ups, developing human resources in the ICT sector, and ensuring an active government role in creating policies that support the growth of this sector. Through this holistic approach, DKI Jakarta can maximize the potential of ICT to achieve sustainable, inclusive and competitive economic growth at the national and international levels.